2003
DOI: 10.2105/ajph.93.3.418
|View full text |Cite
|
Sign up to set email alerts
|

African American Women and Smoking: Starting Later

Abstract: It is commonly accepted that adolescence is the period for initiation into smoking and other tobacco use behaviors. However, evidence is increasing that the set of presumptions about adolescent onset of tobacco use may not be true for all cultural or subpopulation groups. Secondary analysis of data from the 2000 National Health Interview Survey (NHIS) was used to examine ethnic differences in smoking patterns among African American and White women. Results showed a striking racial/ethnic difference in age of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 8 publications
2
37
1
Order By: Relevance
“…Smoking initiation during the late teens and early adulthood is also an important public health issue because these ages coincide with the peak childbearing and child-rearing ages. 8 The present results suggest prevention and intervention efforts need to consider individual groups (not just overall averages) and tobacco control efforts need to be targeted beyond the teenage years. For instance, one suggested US tobacco policy is to raise the minimum age for legal access to cigarettes from 18 to 21; analyses on the impact of such policies need to consider race, to test whether they are more effective among whites than other racial/ethnic groups, with the potential consequence of widening tobacco-related health disparities.…”
Section: Moving Forwardmentioning
confidence: 83%
See 1 more Smart Citation
“…Smoking initiation during the late teens and early adulthood is also an important public health issue because these ages coincide with the peak childbearing and child-rearing ages. 8 The present results suggest prevention and intervention efforts need to consider individual groups (not just overall averages) and tobacco control efforts need to be targeted beyond the teenage years. For instance, one suggested US tobacco policy is to raise the minimum age for legal access to cigarettes from 18 to 21; analyses on the impact of such policies need to consider race, to test whether they are more effective among whites than other racial/ethnic groups, with the potential consequence of widening tobacco-related health disparities.…”
Section: Moving Forwardmentioning
confidence: 83%
“…4,[6][7][8] This pattern is varyingly referred to as a "crossover" 9,10 or "convergence" in smoking. 11,12 Many factors may explain this racial convergence in smoking.…”
mentioning
confidence: 99%
“…Several recent studies have shown that a sizeable proportion of AfricanAmerican smokers begin smoking after age 18 [38,39]. For example, Moon-Howard [39] reported that and African-American women begin smoking, on average, one year later than non-Hispanic white women.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that a sizeable proportion of AfricanAmerican smokers begin smoking after age 18 [38,39]. For example, Moon-Howard [39] reported that and African-American women begin smoking, on average, one year later than non-Hispanic white women. Most studies report that smoking initiation is largely a youth behavior [1], but our finding underscores the need to develop smoking initiation prevention programs specifically for young African-American adults.…”
Section: Discussionmentioning
confidence: 99%
“…The age when a person starts to smoke cigarettes regularly may be associated with addiction and may be disregarded by persons who do not consider themselves to be regular smokers 67 . As noted previously, African Americans tend to initiate tobacco use later in life 26 , 68 , 69 compared with whites and are more likely to be nondaily smokers 70 . Thus, it is important to evaluate measures of age of initiation of tobacco use among African Americans.…”
Section: Methodsmentioning
confidence: 99%